The Influence of Influencers on Purchasing Decisions with the Mediating Role of Value and Perceived Emotions on Tiktok Live - Ramadhan, Maulana; Julianti, Rosita; Hernidatiatin, Lis Tatin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the influence of influencers on purchasing decisions, with perceived value and emotions as mediators, in the context of TikTok Live. Live streaming significantly impacts consumer behavior, requiring influencers to build emotional engagement and deliver product value effectively. Using a quantitative method with an online survey of 180 respondents, data were analyzed with SmartPLS 3. Results indicate that influencers positively and significantly affect purchasing decisions (t = 13.125; p = 0.000). Perceived value and emotions mediate this relationship substantially (t = 4.054 and 2.224; p = 0.000 and 0.027). The F-test confirms a simultaneous significant effect of all variables. This study contributes to digital marketing literature by emphasizing emotional and value-driven mechanisms in influencer-based live-streaming commerce.